2016
DOI: 10.1507/endocrj.ej15-0482
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent changes in insulin requirement for maternal glycemic control during antenatal corticosteroid therapy in women with gestational diabetes: a retrospective study

Abstract: Abstract. Though recommended for pregnant women at risk of preterm birth to improve perinatal outcomes, antenatal corticosteroid (ACS) treatment can cause maternal hyperglycemia, especially in cases of glucose intolerance. A standardized protocol for preventing hyperglycemia during ACS treatment remains to be established. We herein retrospectively investigated the time-dependent changes in insulin dose required for maternal glycemic control during ACS treatment in gestational diabetes (GDM). Twelve singleton p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Marked between-trial heterogeneity in setting (early vs. late gestation) and steroid (prednisolone, dexamethasone or betamethasone), and small numbers, preclude significant analysis of efficacy, with no reported data on neonatal hypoglycaemia. Itoh and colleagues [27] demonstrated that intravenous insulin (IVI) infusions can be highly effective for controlling maternal glycaemia following betamethasone (on-IVI glucose 3.9-8.3 mmol/l in 12 women with gestational diabetes), although infusion rates were adjusted individually by attending physicians and no protocol was published. The Joint British Diabetes Societies for Inpatient Care (JBDS-IP) recent guideline proposes a variable rate IVI infusion for the management of glycaemic excursions following betamethasone, and although audit parameters are provided, audit data are not yet available [19].…”
Section: Introductionmentioning
confidence: 99%
“…Marked between-trial heterogeneity in setting (early vs. late gestation) and steroid (prednisolone, dexamethasone or betamethasone), and small numbers, preclude significant analysis of efficacy, with no reported data on neonatal hypoglycaemia. Itoh and colleagues [27] demonstrated that intravenous insulin (IVI) infusions can be highly effective for controlling maternal glycaemia following betamethasone (on-IVI glucose 3.9-8.3 mmol/l in 12 women with gestational diabetes), although infusion rates were adjusted individually by attending physicians and no protocol was published. The Joint British Diabetes Societies for Inpatient Care (JBDS-IP) recent guideline proposes a variable rate IVI infusion for the management of glycaemic excursions following betamethasone, and although audit parameters are provided, audit data are not yet available [19].…”
Section: Introductionmentioning
confidence: 99%
“…The diabetogenic potential of BM is known, and combined with placental insulin resistance in pregnancy, leads to a transient increase in the blood glucose levels of pregnant women [7,8]. Few small studies in the literature exist regarding the action of BM on glucose homeostasis in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Great attention is paid to the group of pregnant women who have either pre-existing diabetes or gestational diabetes, and especially those under insulin therapy. In this case, it is recommended, by limited bibliographic data, to up-titrate the insulin dose by 30%-40% in order to prevent very high blood glucose levels, which may exacerbate an already at-risk pregnancy (hydramnios) [7][8][9][10][11][12][13][14][15][16]. Furthermore, hyperglycemia can lead to severe neonatal hypoglycemia in the case of preterm delivery [7,9,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations